Synergistic effects of baicalein with cefotaxime against Klebsiella pneumoniae through inhibiting CTX-M-1 gene expression. Issue 1 (December 2016) - Cai, Wenhui; Fu, Yingmei; Zhang, Wenli; Chen, Xiaobei; Zhao, Jizi; Song, Wuqi; Li, Yujun; Huang, Ying; Wu, Zheng; Sun, Rui; Dong, Chunping; Zhang, Fengmin
Abstract Background Generation of extended- spectrum β- lactamases is one of the major mechanisms by which clinicalKlebsiella pneumoniae develop resistance to antibiotics. Combined antibiotics prove to be a relatively effective method of controlling such resistant strains. Some of Chinese herbal active ingredients are known to have synergistic antibacterial effects. This study is aimed to investigate synergistic effects of Chinese herbal active ingredients with cefotaxime on the extended- spectrum β- lactamase positive strains ofKlebsiella pneumoniae, and to analyze mechanism of synergistic action, providing experimental evidence for clinical application of antimicrobial drugs. Results For total sixteen strains including fifteen strains of cefotaxime resistantK. pneumoniae and one extended- spectrum β- lactamase positive standard strain, the synergy rates of cefotaxime with baicalein, matrine, and clavulanic acid were 56.3 %, 0 %, and 100 %, respectively. The fractional inhibitory concentration index of combined baicalein and cefotaxime was correlated with the percentage decrease of cefotaxime MIC of all the strains (r  = −0.78, p <0.01). In the group of synergy baicalein and cefotaxime, the transcribed mRNA level of CTX-M-1 after treatment of baicalein was decreased significantly (p <0.05). Moreover, the CTX-M-1 mRNA expression percentage inhibition (100 %, 5/5) was significantly higher than non- synergy group (25 %, 1/4) (p <0.05). Conclusions Our study demonstrated that baicalein exhibited synergistic activity when combined with cefotaxime against some of extended- spectrum β- lactamases positiveK. pneumoniae strains by inhibiting CTX-M-1 mRNA expression. However, no direct bactericidal or bacteriostatic activity was involved in the synergistic action. Baicalein seems to be a promising novel effective synergistic antimicrobial agent.